Using Subthreshold Vibratory Stimulation During Poststroke Rehabilitation Therapy: A Case Series. (January 2022) - Vatinno, Amanda A.; Hall, Lucion; Cox, Hannah; Fluharty, Alison; Taylor, Catilyn; Wease, Alexandra; Davis, Allison; Cain, Shannon; Ramakrishnan, Viswanathan; Woodbury, Michelle; Seo, Na Jin
Subthreshold vibratory stimulation to the paretic wrist has been shown to prime the sensorimotor cortex and improve 2-week upper extremity (UE) therapy outcomes. The objective of this work was to determine feasibility, safety, and preliminary efficacy of the stimulation over a typical 6-week therapy duration. Four chronic stroke survivors received stimulation during 6-week therapy. Feasibility/safety/efficacy were assessed at baseline, posttherapy, and 1-month follow-up. For feasibility, all participants wore the device throughout therapy and perceived the stimulation comfortable/safe. Regarding safety, no serious/moderate intervention-related adverse events occurred. For efficacy, all participants improved in Wolf Motor Function Test and UE use in daily living based on accelerometry and stroke impact scale. Mean improvements at posttherapy/follow-up were greater than the minimal detectable change/clinically important difference and other trials with similar therapy without stimulation. In conclusion, the stimulation was feasible/safe for 6-week use. Preliminary efficacy encourages a larger trial to further evaluate the stimulation as a therapy adjunct.